In vivo analysis of concentration-dependent effects of halothane or isoflurane inhalation on the electrocardiographic and hemodynamic variables in dogs - Hiroyuki Saito; Ryuichi Kambayashi; Ai Goto; Mihoko Hagiwara-Nagasawa; Kiyotaka Hoshiai; Yoshio Nunoi; Hiroko Izumi-Nakaseko; Yasuki Akie; Yoshinori Takei; Akio Matsumoto; Atsushi Sugiyama (Elsevier, 2021)
We assessed concentration-dependent effects of halothane or isoflurane inhalation on the electrocardiographic and hemodynamic variables using a cross-over design in intact beagle dogs (n = 4). Elevation of inhaled halothane from 1.0% to 2.0% or isoflurane from 1.5% to 2.5% decreased the mean blood pressure and prolonged the QRS width without significantly altering the heart rate, PR interval or QT interval. However, the observed changes disappeared after regressions of both anesthetic conditions to their initial settings. These results indicate that hypotension-induced, reflex-mediated increase of sympathetic tone may have counterbalanced the direct negative chronotropic, dromotropic and repolarization slowing effects of the anesthetics.